Design and plantwide control of n-butyl acrylate production process. (October 2017) - Moraru, Mihai Daniel; Bildea, Costin Sorin
Graphical abstract: Highlights: Conventional reactor-separation-recycle processes for n -butyl acrylate using solid catalyst are controllable. The reactor operating point is selected using bifurcation diagrams. The difficult acrylic acid/ n -butyl acrylate split is achieved by extractive distillation. The performance of the control scheme is proved by rigorous dynamic simulation. Abstract: n -Butyl acrylate is commercially produced from acrylic acid and n -butanol using strong acidic homogeneous catalysts. To overcome problems related to corrosion, catalyst removal from product and catalyst disposal after neutralization, research based on solid catalysis received increased attention in the recent years. However, design and control studies of an entire plant are rare. In this paper, the design and control of two reaction-separation-recycle process alternatives are developed. Both use a fixed-bed reactor with Amberlyst 131 catalyst. The separation of n -butyl acrylate from the mixture with n -butanol and acrylic acid is difficult. One of the process alternatives achieves the separation by distillation at pressure above atmospheric, while the other conveniently employs extractive distillation with ethylene glycol. Both processes are controllable, the control system showing robustness when increase or decrease in production capacity is required, or operating conditions change. Aspen Plus and Aspen Plus Dynamics are used as efficient Computer-Aided Process Engineering tools.